Validity and reliability of the Japanese Interest Checklist for the Elderly. (July 2016) - Nakamura-Thomas, Hiromi; Kyougoku, Makoto; Taylor, Renee
Introduction: The validity and reliability of the Japanese Interest Checklist for the Elderly were examined. Method: 687 participants responded, using the new scale system: 'currently participate based on interest, ' 'participate less because of health status' or 'no interest.' The convergent and discriminant validity of the factorial structure were examined using two-stage Confirmatory Factor Analysis approaches. The discriminant validity and reliability of the scale system were examined using two-stage Item Response Theory approaches. Results: The first Confirmatory Factor Analysis stage indicated values representing good (factor loadings: 0.99–0.75; Comparative Fit Index: 0.99; Tucker-Lewis Index: 0.98) to adequate (Root Mean Square Error of Approximation: 0.054) fit levels. Both the discriminant validity and convergent validity were identified to be high. The second Confirmatory Factor Analysis stage with a Path analysis and consideration of age and gender indicated values representing a good fit (factor loadings: 0.99–0.78; Comparative Fit Index: 0.99; Tucker-Lewis Index: 0.98; Root Mean Square Error of Approximation: 0.048). The first Item Response Theory stage indicated the values for the discriminant validity in the expected ranges; however, it displayed lower reliability in some activities. The second Item Response Theory state with the latent-class model-based multi-group Item Response Theory confirmed the pattern of invariance. Conclusion: The factorial structure was valid across different groups of people. The scale system has to be improved.